Very long-chain acyl-CoA dehydrogenase deficiency revisited: a retrospective genotype–phenotype analysis in a Saudi tertiary center - Alhumaidi, Suzan Suliman; Algaeed, Fahad Abdulrahman; Aladhadh, Meshari Fayez; Alkaff, Sara Abdulrahman (Frontiers in Genetics, 2025)
IntroductionIn this retrospective study, we analyzed clinical, biochemical, and genetic data and examined correlations between prevalent variants and outcomes of very long-chain acyl-CoA dehydrogenase (VLCAD) deficiency.MethodsPatients with VLCAD deficiency confirmed through molecular genetic testing at King Saud Medical City, Riyadh, Saudi Arabia, between 2016 and 2023 were included. Patients presented in the neonatal period with abnormal newborn screening and with metabolic decompensation and biochemical abnormalities clinically.ResultsVLCAD deficiency was confirmed in 14 children. The mean age at presentation was 5.6 days. Clinically, 10 of the 14 patients presented with rhabdomyolysis. Hepatomegaly was observed in 9, cardiomyopathy in 7, and hypoglycemia in seven patients. In total, three variants were detected in the 14 patients: c.1310A>C (p.Glu437Ala) in 2; c.134C>A (p.Ser45X) in 6; and c.65C>A (p.Ser22Ter) in six patients. Currently, 12 patients are alive, whereas two have died. No significant relationship was identified between genotype and survival (P = 0.719). Variant C.1310A was associated with an excellent prognosis. Unlike those in other studies, variants c.65C>A and c.134C>A were associated with poor outcomes and early presentation with metabolic decompensation.DiscussionLong-term, prospective studies integrating metabolic profiling, functional assays, and multi-omics approaches will be essential to unravel the complex interplay between genetic variants and clinical expression and prognostic outcomes in VLCAD deficiency.